Dysregulated Ca2+-Permeable AMPA Receptor Signaling in Neural Progenitors Modeling Fragile X Syndrome - Danesi, Claudia; Keinänen, Kari; Castrén, Maija L. (Frontiers in Synaptic Neuroscience, 2019)
Fragile X syndrome (FXS) is a neurodevelopmental disorder that represents a common cause of intellectual disability and a variant of autism spectrum disorder (ASD). Studies that have looked for similarities in syndromic and non-syndromic forms of ASD have paid special attention to alterations of maturation and function of glutamatergic synapses. Copy number variations (CNVs) in the loci containing genes encoding alpha-amino-3-hydroxy-5-methylisoxazole-4-propionic acid receptors (AMPARs) subunits have been associated with ASD in genetic studies. In FXS, dysregulated AMPAR subunit expression and trafficking affect neural progenitor differentiation and synapse formation as well as neuronal plasticity in the mature brain. Decreased expression of GluA2, the AMPAR subunit that critically controls Ca2+-permeability, and a concomitant increase in Ca2+-permeable AMPARs (CP-AMPARs) in human and mouse FXS neural progenitors parallels changes in expression of GluA2-targeting microRNAs (miRNAs). Thus, posttranscriptional regulation of GluA2 by miRNAs and subsequent alterations in calcium signaling may contribute to abnormal synaptic function in FXS as well as, by implication, in some forms of ASD.